Utility of image guided fine needle aspiration cytology in intra-thoracic lesions with emphasis on lung cancer detection - Geeta Pachori; Supriya Singh Toor; Rashmi Sharma; Tushar Bayla (Journal of Cytology, 2020)
Background and Aims: Fine Needle aspiration cytology has emerged as an essential pre-biopsy investigation to rule out or confirm malignancy in superficial as well as deep seated lesions. Radiological assistance has proved to be a blessing for obtaining adequate samples. With unwavering leading position of lung cancer in terms of incidence and mortality, it has become necessary to study the trends of our population and assess the usefulness of techniques aiding in early diagnosis. The objective is to obtain prevalence of lung cancer and utility of various methods in obtaining cytological material for assessment in intrathoracic lesions. Material and Methods: We conducted an observational analytic study at a tertiary care teaching hospital over a period of 3.5 years including a total of 307 patients with suspected lung malignancy. Samples were collected using image guided techniques including Fibre-optic bronchoscopy (FOB), Ultra-sonography (USG) and Computed tomography (CT). The smears were processed as per standard institutional protocol and were evaluated by a senior pathologist. Results: Squamous cell carcinoma was the most frequent type of Primary lung malignancy, followed by adenocarcinoma. The malignancies were more common in males and in age group of 61 to 70 years. Conclusion: Respiratory cytology remains the initial mode of investigation in intra-thoracic malignancies. The high sensitivity, low-cost and rapidity of the results works its advantages for both the patient and the clinician. High cellular yield obtained with the use of trans-bronchial needle aspiration and bronchial brushing rationalizes their use as a screening test to establish both malignant as well as non-malignant diagnoses. Further improvement in utilization of the available modalities and addition of ancillary testing can reduce the need of invasive procedures.